Charles Wright Mills, Wyobraźnia socjologiczna (przeł. M. Bucholc, red. przed. do wyd. pol. J. Mucha), Wydawnictwo Naukowe PWN, Warszawa 2009, ss. 376 - Panfil, Rafał Bartłomiej (Studia Mazowieckie, 2025)
Artykuł recenzyjny.